Interreligious hermeneutics in pluralistic Europe : between texts and people - Cheetham, David (David A.) (Currents of encounter, 2011)
At the second major conference held in Salzburg in 2009 of The European Society for Intercultural Theology and Interreligious Studies (ESITIS), participants probed the broad theme of 'interreligious hermeneutics in a pluralistic Europe'. Due to the phenomenon of an increasingly plural Europe, questions arise about how we see each other's cultural heritage, religious traditions and sacred scriptures. Following the discussions that took place at the conference, this book focuses on the usage of texts in our global and mass media world, the possibility of 'scriptural reasoning', the theological co.